Pemanfaatan SEO (Search Engine Optimization) dalam meningkatkan Penjualan Produk Speaker X9 Pro Audio dalam Kewirausahaan Bidang Pendidikan - Tonyjanto, Christian; I Gusti Putu Sudiarta, I Gusti Putu; Sutajaya, I Made; Prawira Kusuma, Agus Tommy Adi; Kurnia Amadea, Ida Bagus Neo (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2024)
SEO has long been known by many people, with the aim of increasing the number of visitors on networking pages. Where the network page, has information in the form of goods, products or services offered. In the research conducted, SEO is specifically designed to market products in the form of speaker goods which have the aim of introducing students to entrepreneurship training with business capital that is not large, but can generate and carry out small entrepreneurship. By building small entrepreneurship, training students to get to know digital marketing with the help of using an application from Tokopedia. The learning process is carried out using the simple ADDIE method to be able to understand and prepare the product to be offered